1999
DOI: 10.1590/s0037-86821999000200008
|View full text |Cite
|
Sign up to set email alerts
|

O peso do baço em chagásicos crônicos

Abstract: Resumo O baço pode aumentar de tamanho nas inflamações com repercussões sistêmicas e na congestão venosa crônica, denominando-se respectivamente, hiperplasia reacional e e s p l e n o m e g a l i a congestiva.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In an earlier report, 15 we described a significant increase in spleen weight in chagasic cases without congestive heart failure in comparison to nonchagasic cases without congestive heart failure, in groups of Chagas' disease or non-Chagas' disease individuals, with or without congestive heart failure, and homogenized relation to age, sex, color, and body mass index. We concluded that the inflammatory component in Chagas' disease plays an important role in the increase of spleen weight together with hemodynamic alterations arising from congestive heart failure.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…In an earlier report, 15 we described a significant increase in spleen weight in chagasic cases without congestive heart failure in comparison to nonchagasic cases without congestive heart failure, in groups of Chagas' disease or non-Chagas' disease individuals, with or without congestive heart failure, and homogenized relation to age, sex, color, and body mass index. We concluded that the inflammatory component in Chagas' disease plays an important role in the increase of spleen weight together with hemodynamic alterations arising from congestive heart failure.…”
Section: Discussionmentioning
confidence: 68%
“…Nevertheless, the areas of these follicles, as well as the congestion of the sinusoids, were significantly greater among the chagasic cases. These data apparently indicate that, because of the increase in spleen weight 15 and possibly its size, there would be greater dispersion of the follicles, thus justifying the lesser density. On the other hand, although "a certain degree of atrophy of the follicles" has previously been described in cases of chronic passive hyperemia, 7 hyperplasia of the white 10.3 ± 1.0 Chagasic without CHF (n ‫ס‬ 17)…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In experimental T . cruzi infection, splenomegaly is associated with increased polyclonal T-cell activation, a hallmark of not regulated immune response [ 6 , 9 , 38 ]. Notably, the splenomegaly seen in Colombian-infected C57BL/6 mice [ 9 , 15 ] was partially reversed by PTX therapy.…”
Section: Discussionmentioning
confidence: 99%